Technológie suchého obaľovania - Garajová, Michaela; Franc, Aleš; Muselík, Jan; Vetchý, David (Chemické listy, 2020)
Dry coating is often used technology for preparation of solid pharmaceutical forms. It brings more benefits than the typically used wet coating technology. The powder, which is used as coating material, can be used immediately, has less environmental impact and enhances mechanical and aesthetic properties of final pharmaceutical form. Many technologies have been developed, being generally classified into the following types: compression coating, hot-melt coating, supercritical fluid coating, plasticizer dry coating, electrostatic dry coating, photocurable dry coating and modified plasticizer-electrostatic-heat dry coating. This review summarizes basic principles of dry coating technologies, their benefits and disadvantages and provides a comparison of them.
Keywords: statická elektřina; prášky, zásypy, pudry; Freezing; Light; polymerizace; Powders; Gases; Static Electricity; světlo; plyny; enterosolventní tablety; Tablets, Enteric-Coated; tlak; Pressure; jedlé filmy; Plastics; Temperature; zmrazování; plastické hmoty; Edible Films; teplota; Polymerization